2014
DOI: 10.1182/blood-2014-02-558163
|View full text |Cite
|
Sign up to set email alerts
|

Baboon envelope pseudotyped LVs outperform VSV-G-LVs for gene transfer into early-cytokine-stimulated and resting HSCs

Abstract: Key Points New LVs allow transduction of unstimulated hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 69 publications
(81 reference statements)
3
142
0
Order By: Relevance
“…Importantly, the H/F-LVs were able to efficiently transduce unstimulated hCD34 1 cells at levels not reported before (40% to 70%) after a single exposure at low vector doses (MOI, 10; Figure 2A). As we previously described, 12,42,43 the VSV-G-LVs were unable to transduce efficiently resting hCD34 1 cells (Figure 2A). In contrast to cytokine-prestimulated hCD34 1 cells, their resting counterparts require at least an MOI of 10 for efficient H/F-LV transduction ( Figure 1E-F vs Figure 2B).…”
Section: Conditioning and Reconstitution Of Nsg Micementioning
confidence: 94%
See 2 more Smart Citations
“…Importantly, the H/F-LVs were able to efficiently transduce unstimulated hCD34 1 cells at levels not reported before (40% to 70%) after a single exposure at low vector doses (MOI, 10; Figure 2A). As we previously described, 12,42,43 the VSV-G-LVs were unable to transduce efficiently resting hCD34 1 cells (Figure 2A). In contrast to cytokine-prestimulated hCD34 1 cells, their resting counterparts require at least an MOI of 10 for efficient H/F-LV transduction ( Figure 1E-F vs Figure 2B).…”
Section: Conditioning and Reconstitution Of Nsg Micementioning
confidence: 94%
“…44,66,68,69 Very recently we demonstrated that a new LV pseudotype carrying the Baboon envelope gp's at their surface (BaEV-LVs) outperformed VSV-G-LVs for hHSC transduction. 43 BaEV-LVs and H/F-LVs manage to transduce resting hHSCs up to 30% and 70%, respectively. H/F-LVs achieved transduction levels never before reached in these resting targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a high viral exposure combined to cytokine stimulation could promote mutagenesis and multicopy integration (44). As an alternative strategy, the recent use of a lentiviral vector pseudo-typed with a baboon retroviral envelope glycoprotein resulted in a higher transduction efficiency in quiescent CD34 + , at a low concentration without any cytokine stimulation (53). Altogether, the safety of these different approaches remains questionable.…”
Section: Gt: a Brief Insight Into A Bright Futurementioning
confidence: 99%
“…1 A utologous transplantation using genecorrected HSCs is achieving a growing number of clinical successes for the treatment of primary immune deficiencies, lysosomal storage and metabolic disorders, and hemoglobinopathies. 2,3 Despite the gratifying progress, it remains challenging to achieve optimal gene transfer to human HSCs, and 10-to 100-fold higher amounts of vectors are typically needed for their gene modification different envelopes to pseudotype the vectors for optimal target HSC binding and entry.…”
mentioning
confidence: 99%